Some questions of institute of specialized Commissioners for Human Rights (Journal of actual problems of jurisprudence, 2018)
The institution of specialized ombudspersons is considered in the given article. The history of the institution of specialized ombudspersons is paid attention to as well. The author notes that the institution of specialized ombudspersons can be created to protect the specific rights and legal interests of a narrow circle of people. Legal status of specialized Commissioners for Human Rights in Kazakhstan has been analyzed, such as: children’s rights ombudsman, the Commissioner for the Protection of the rights of entrepreneurs, investment ombudsman, banking ombudsman and insurance ombudsman.Key words: Institution, Commissioner for Human Rights, the protection of the rights, the rights of entrepreneurs, legal status.